MODEL DEVELOPMENT OF OPERATIONAL RISK MITIGATION STRATEGY BASED ON ORGANIZATIONAL LIFE CYCLE AND STAKEHOLDERS AT MICRO, SMALL, AND MEDIUM ENTERPRISE: HISTORICAL CASE STUDY THE MACHINERY AND MECHANICAL TOOLS INDUSTRY SECTOR FOR METALWORK - Suryati, Asih
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy. Although MSME dominates the business in Indonesia, MSME contributions to national GDP are not proportional to the number of existing businesses. Therefore, Indonesia's government is trying to focus on several priority industries, one of which is the machinery and machine tool industry for metalworking. This industry is a supporting industry for the metal-based manufacturing industry sector. In fact, MSMEs face various uncertainties in developing their businesses which can threaten their survival. Moreover, MSME organizations often face changes in the demands of their key stakeholders. In addition, The inability to meet those demands will create risks that can threaten MSME organizational goals. MSME organizations have limited resources and capabilities. Without an appropriate risk mitigation strategy framework for MSME organization context, there is a possibility that the applied risk mitigation activities are not optimal. In this study, risk is defined as an event that if it occurs can have a detrimental effect or negative on the achievement of organizational goals. Operational risks include risks that occur in the organization's business processes related to the organization's stakeholders. Operational risk mitigation strategy frameworks that are appropriate to the context of MSME organizations can be a solution so that MSME organizations can survive, grow, and develop. This study aims to develop operational risk mitigation strategies frameworks based on organizational life cycle and dependency structure with its stakeholders in machinery and mechanical tools industry sector for metalwork MSMEs. The research model was developed by applying two different constructs in dependency structure, which is dependence asymmetry and mutual dependence. Not only customer and supplier, the model was also developed to examine dependency structure between organization and employee. The stages of this research are identifying the growth stage of the organization, identifying stakeholders involved and risks in the core business processes of MSMEs in the metalworking machinery